Vestigios y sombras de Jean D´Agreve. La enfermedad de las horas y el mal de vivir - Paladines Cabrera, Arturo Vinicio (2015)
This research work has been titled “TRACE AND SHADOWS OF JEAN D'AGREVE. DISEASE OF THE HOURS AND EVIL LIVE”. Aimed at presenting the social idea, influence and evasive, progressive idea of French symbolist poet poetry in Guayaquil. The following general objective was made in the development of this theme: Spread the unknown journalistic work of Jean d'Agreve in our midst. The methodology is being used in scientific, descriptive, inductive method - deductive, analytical - synthetic, and as a literary method the narratological; likewise has the relevant technical literature has been used. The results can determine the following conclusions: a large influence of French symbolist literature evidence, especially writers like Rimbaud, Baudelaire, Verlaine, of whom learned musicality, rhythm, social idea to the poor, prostitutes and the most vulnerable creatures of society; a harsh critique of the bourgeoisie and the formalities. Evasive and depressive ideas that are a constant in the poetry of Silva and French masters; Aesthetic refinement; exalt the beauty of the horrible and terrible beauty; literary and journalistic ignorance of Silva has set a terrible forgetting his chronicler work, this fact lies primarily in that its readers, has turned attention to the fact of his death, often exorcised, drugs and bohemian life. As such the following recommendations are raised; poetry is not made to stay between the lines; must be understood and mostly lived, poetry Silva must leave the libraries and the windows and take it to the street, experiences and emotions, only then will a better place this world, which is so far made of mud and trash, if we foster a culture of sensitivity have new children, new young; slow and thoughtful reading done by alumnus and faculty, hechar a new look at our poets, who despite having led a bohemian and sometimes dreary life, is our essence; and our own soul, is written on those paragraph